Marked increase in the incidence of anterior cruciate ligament reconstructions in young females in New Zealand. Issue 9 (26th August 2019) - Sutherland, Kirsty; Clatworthy, Mark; Fulcher, Mark; Chang, Kevin; Young, Simon W.
Abstract: Background: Anterior cruciate ligament injuries cause significant morbidity, and may be increasing in incidence as participation in high‐risk sports increases. The aim of this study is to investigate the incidence of anterior cruciate ligament reconstruction (ACLR) surgery in New Zealand, and to analyse changes over time in demographic subgroups. Method: Data were sourced from the Accident Compensation Corporation. Data relating to primary ACLRs performed from 2009 to 2016 were evaluated ( n = 20 751). Baseline population estimates were obtained from national census data to calculate the incidence, and results were compared to previous data from 2000 to 2005 ( n = 7375). Results: The annual incidence of ACLR for 2009–2016 was 58.2 per 100 000 person‐years and was greater in males than in females (72.2 and 44.9, respectively). This represents a 58% increase when compared with the period 2000–2005 (36.9 per 100 000). The greatest increase was seen in females aged 15–19 years, with the incidence increasing by 120% in the last decade, compared with 53% in females aged 20–24 years. The percentage of injuries caused by sports changed from 65% over 2000–2005 to 76% over 2009–2016, with netball, rugby and football accounting for the highest number of injuries. Conclusion: The incidence of ACLR procedures has increased markedly in New Zealand, and this increase was most pronounced in females aged 15–19 years. A greater proportion of procedures are now due to sport‐related injuries. Abstract : We found a 120% increase in the incidence of anterior cruciate ligament reconstruction surgery in young females in New Zealand from 2000–2005 to 2013–2016. A higher proportion of anterior cruciate ligament reconstruction in New Zealand are now due to sport‐related causes, particularly netball, rugby and football. Injury prevention strategies should target these high‐risk groups, especially young females.